Hydrophobic Forces Measured Between Silica Surfaces Coated With CnTACi Homologues (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
An Atomic Force Microscope (AFM) was used to measure the surface forces between glass sphere and silica plate in CnTAC1 (n=12, 14, 16, 18) solutions. The results showed the presence of long-range attractive forces that can be fitted to single exponential functions. With a given surfactant, the attractive force increased with increasing concentration, and reached a maximum at the point of charge neutralization (p.c.n.). The decrease in the attractive force above the p.c.n. is probably due to the inverse orientation of the surfactant molecules. A plot of the log (p.c.n.) vs. the number of carbons in the hydrocarbon chains of the Cn TACI homologues showed a linear relationship with a slope of -0.37, indicating that the surfactant adsorption entails a decrease in free energy by -0.85 kT per mole of CH2 (or CH3) group. These results suggest that the adsorption of long-chain surfactants is controlled by hydrocarbon chain association during the process of forming surface hemi-micelles (or domains). Possible origins of the long-range attractions are discussed on the basis of the results presented in this communication.